2013 IEEE 14th Workshop on Control and Modeling for Power Electronics (COMPEL) 2013
DOI: 10.1109/compel.2013.6626403
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Hardware-in-the-Loop simulation of convertible static transmission controller for transmission grid management

Abstract: We propose a Convertible Static Transmission Controller (CSTC) concept that enables coordinated power flow control with emphasis on large penetration of renewable energy resources based transmission in a meshed network. CSTS can be connected across the substation power transformer and reconfigured for different modes of operation to perform as a versatile transmission controller with several functions including: power flow control for transmission of renewable resources, and as a transformer back-up for disast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This allows the system to be emulated in software, while connecting with real-world hardware in real time [22]. Using an HIL approach allows the proposed control method to be tested virtually with an example system, while interfacing with real hardware [23].…”
Section: Hardware-in-the-loop Resultsmentioning
confidence: 99%
“…This allows the system to be emulated in software, while connecting with real-world hardware in real time [22]. Using an HIL approach allows the proposed control method to be tested virtually with an example system, while interfacing with real hardware [23].…”
Section: Hardware-in-the-loop Resultsmentioning
confidence: 99%
“…In order to validate the simulation results presented in the previous section, the example microgrid shown in Figure 8 was implemented using a hardware-in-the-loop (HIL) system, allowing the system to be emulated in software, and connected with real world hardware in real time [20]. Using an HIL approach allows the system to be built and tested virtually with new proposed control methods, while interfacing with real hardware [21].…”
Section: Hardware-in-the-loop Resultsmentioning
confidence: 99%
“…Research that used CHIL tests as a basis for converter design have also been reported for slow-switching power converters [6], [7]. Multiple papers have been published on CHIL application for power converters in power systems [8], [9]. These studies either do not implement a switching-level model for the power converter or have a slow real-time simulation for the system, which prevents accurate modeling of the fast-switching dynamics realized by the advent of wide bandgap device-based power converters.…”
Section: Introductionmentioning
confidence: 99%